Vascular Occlusions following Ocular Surgical Procedures: A Clinical Observation of Vascular Complications after Ocular Surgery - Charlotte Fischer; Anne Bruggemann; Annette Hager; Josep Callizo Planas; Johann Roider; Hans Hoerauf (Journal of Ophthalmology)
Background. Ocular vascular occlusions following intraocular procedures are a rare complication. We report a case series of patients with retinal vascular occlusions or anterior ischemic optic neuropathy (AION) after anterior and posterior segment surgery and demonstrate possible risk factors. Methods. Observational case series. Results. In ten patients, vascular occlusions were observed within ten weeks after intraocular surgery: branch retinal arterial occlusion (BRAO) (n=2), central retinal artery occlusion (CRAO) (n=2), central retinal vein occlusion (CRVO) (n=1), branch retinal vein occlusion (BRVO) (n=1), anterior ischemic optic neuropathy (AION) (n=3), and combined central artery and vein occlusion (n=1). AION occurred later (27–69 d) than arterial occlusions (14–60 d) or venous occlusions (1-2 d). In all cases, either specific surgical manipulations or general vascular disorders were identified as risk factors. In addition to general cardiovascular risk factors (arterial hypertension n=6, diabetes mellitus n=4), internal workup disclosed bilateral stenosis of the carotid arteries (n=1) and myeloproliferative syndrome (n=1). Conclusion. Vascular occlusions after surgical ocular procedures seem to be more frequent when cardiovascular diseases coexist. Surgical maneuvers and intra- or postoperative pressure changes may act as a triggering mechanism in patients with underlying systemic cardiovascular disorders. Affected patients should undergo thorough internal examination to identify possible underlying diseases.